Site-specific orthometallation via C–H bond activation and syntheses of ruthenium(iii) organometallics: studies on nitric oxide (NO) reactivity and photorelease of coordinated NO. Issue 76 (29th July 2016) - Kumar, Rajan; Kumar, Sushil; Bala, Manju; Ratnam, Anand; Singh, U. P.; Ghosh, Kaushik
Abstract : σ-Aryl ruthenium(iii ) complexes were synthesized by C–H bond activation and organometallic nitrosyl complexes were synthesized and characterized by spectroscopy and crystal structure. Coordinated NO molecule was found to be photolabile. Abstract : A new family of σ-aryl ruthenium(iii ) complexes [Ru(L 1–4 )(PPh3 )2 Cl] (1–4 ) (where L 1 H2 = N -(quinolin-8-yl)benzamide for1, L 2 H2 = 4-chloro- N -(quinolin-8-yl)benzamide for2, L 3 H2 = 4-nitro- N -(quinolin-8-yl)benzamide for3, L 4 H2 = 3-nitro- N -(quinolin-8-yl)benzamide for4 and H = dissociable protons) derived from bidentate ligands having amide bonds was synthesized through C–H bond activation. These organometallic ruthenium(iii ) complexes were treated with nitric oxide (NO) to afford the nitrosyl complexes [Ru(NO2 L 1–4 )(PPh3 )2 (NO)](ClO4 ) (1a–4a ) (where NO2 L 1 H2 = N -(5-nitroquinolin-8-yl)benzamide for1a, NO2 L 2 H2 = 4-chloro- N -(5-nitroquinolin-8-yl)benzamide for2a, NO2 L 3 H2 = 4-nitro- N -(5-nitroquinolin-8-yl)benzamide for3a, NO2 L 4 H2 = 3-nitro- N -(5-nitroquinolin-8-yl)benzamide for4a and H = dissociable protons). All ruthenium complexes were characterized by various spectroscopic techniques. An X-ray crystallographic study afforded the molecular structure of complex4a and the site-specific ortho metallation was scrutinized. The coordinated NO molecule was found to be photolabile under visible and UV light.